Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

How to solve for x using the equation: 12 = -4 (- 6x - 3)

Sagot :

pik56
I don’t know how to explain it so I am just giving the equation

12=-4(-6x-3x)
Divide both sides by 4
12/4=-4(-6x-3x)/4
3=-4(-6x-3x)/4
3=-(-6x-3x)
3=9x
9x/9 = 3/9
Divide both sides by 9
x=1/3